Vasoactive intestinal peptide excites GnRH neurons via KCa3.1, a potential player in the slow afterhyperpolarization current - Constantin, Stephanie; Quignon, Clarisse; Pizano, Katherine; Shostak, David M.; Wray, Susan (Frontiers in Cellular Neuroscience, 2024)
VIP is an important component of the suprachiasmatic nucleus (SCN) which relays circadian information to neuronal populations, including GnRH neurons. Human and animal studies have shown an impact of disrupted daily rhythms (chronic shift work, temporal food restriction, clock gene disruption) on both male and female reproduction and fertility. To date, how VIP modulates GnRH neurons remains unknown. Calcium imaging and electrophysiology on primary GnRH neurons in explants and adult mouse brain slice, respectively, were used to address this question. We found VIP excites GnRH neurons via the VIP receptor, VPAC2. The downstream signaling pathway uses both Gs protein/adenylyl cyclase/protein kinase A (PKA) and phospholipase C/phosphatidylinositol 4,5-bisphosphate (PIP2) depletion. Furthermore, we identified a UCL2077-sensitive target, likely contributing to the slow afterhyperpolarization current (IAHP), as the PKA and PIP2 depletion target, and the KCa3.1 channel as a specific target. Thus, VIP/VPAC2 provides an example of Gs protein-coupled receptor-triggered excitation in GnRH neurons, modulating GnRH neurons likely via the slow IAHP. The possible identification of KCa3.1 in the GnRH neuron slow IAHP may provide a new therapeutical target for fertility treatments.